If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(-3m-8)=98
We simplify the equation to the form, which is simple to understand
-7(-3m-8)=98
Reorder the terms in parentheses
+(+21m+56)=98
Remove unnecessary parentheses
+21m+56=+98
We move all terms containing m to the left and all other terms to the right.
+21m=+98-56
We simplify left and right side of the equation.
+21m=+42
We divide both sides of the equation by 21 to get m.
m=2
| 10-3(4x-2)=5x | | 4x-9=2x+1 | | 10x-7=5(x+1) | | 4x-29.2=7.5x-6.8 | | 3g-21=20+2g | | 5n=20(4+0.25) | | (X+2)(x^2-1)=0 | | 7685=345-5d | | -51z=-11.73 | | 2243+5754+789= | | 14*(3/2+x)=28 | | x^2+2r-360=0 | | 6x^2-22x-20=0 | | 14(3/2+x)=28 | | 6-0.25f=3 | | 6.4x=0.2816 | | -6t+17=3t-34 | | -23z+234=970 | | 0.4y-8=9-0.6y | | .01x+.10x+.25(31-2x)=3.46 | | 108+4u=2u | | -.8x+2.2=7 | | 5x+21-2x=27 | | -3.7-5x-8.3-2x=-6x+11.4 | | 6.4x=0.2016 | | 4a^2-10=54 | | (72.34)2.1= | | -3(3x+15)-(10-1x)=35 | | 28x-7=26x+7 | | 11x-9+3x-4=10x-2+3x | | 7n^2+10=-75 | | -3(3x+15)-(10-x)=35 |